High prevalence of abdominal aortic aneurysm in patients with inguinal hernia - Megalopoulos, Angelos; Ioannidis, Orestis; Varnalidis, Ioannis; Ntoumpara, Maria; Tsigriki, Lina; Alexandris, Konstantinos; Anastasiadou, Christiana; Styliani, Parpoudi; Paraskevas, George; Mantzoros, Ioannis (Biomedical papers, 2019)
Aims: There is increased prevalence of inguinal hernia (ΙΗ) in patients with abdominal aortic aneurysm (AAA). As there is limited data on AAA in patients with ΙΗ our objective was to examine the prevalence of AAA in such patients. Methods: We prospectively examined 185 consecutive patients for AAA who presented to our department for surgical repair of an ΙΗ. All patients were referred for ultrasound of the abdominal aorta. An AAA was considered to be present when the distal diameter of the abdominal aorta was over 3 cm. Patients with no AAA were followed annually with an abdominal ultrasound for 5 years. Results: Out of the 185 patients (179 males, 6 females) aged from 35-81 (mean 58.6 years), AAA initially appeared in 28 patients with a mean age 61.2 years old. The range of the aortic distal diameter was between 3.4 and 8.1 cm with a mean diameter of 4.8 cm in patients with AAA. The prevalence of the ΑΑΑ was increased in smokers, with hypertension and with bilateral and direct hernia. At the end of the 5 years follow-up, 16 more patients had developed an AAA of mean diameter 3.2 cm (3-4.1 cm), increasing the prevalence of AAA to 27.7%. Conclusion: There is an increased prevalence of AAA in patients with ΙΗ, especially in smokers, with hypertension and with bilateral and/or direct hernia. Hence, periodic ultrasonound may play an important role in screening and early diagnosis of AAA in these patients.
Keywords: abdominal aortic aneurysm; aorta; inguinal hernia; ultrasound; screening